A familial syndrome of microcephaly, sparse hair, mental retardation, and seizures. Issue 2 (February 1990) - van Haeringen, A; Hurst, J A; Savidge, R; Baraitser, M
Abstract : A family is described in which the father and three of his seven children have microcephaly, mild to moderate mental retardation, and sparse hair. The two affected boys have generalised seizures in addition.